2021
DOI: 10.14202/vetworld.2021.2102-2108
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical mastitis: Prevalence and risk factors in dairy cows in East Java, Indonesia

Abstract: Background and Aim: Subclinical mastitis (SCM) is a disease that frequently attacks lactating dairy cows and possibly decreases production, causing economic losses to farmers. This study aimed to define the prevalence of SCM and risk factor-associated related management practice by dairy farmers in East Java, Indonesia. Materials and Methods: The milk sample per quarter of individual lactating Friesian–Holstein cows (592 samples) was collected from 148 cows from 62 selected farms in the region with high dairy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
8
0
1
Order By: Relevance
“…It is estimated that approximately 68% of dairy cattle show an abnormal milk reaction using the CMT technique. This study found that the proportion of DC CMT in individual dairy cattle was similar to that found in Indonesia [ 39 ]; however, in contrast to other studies in Tunisia [ 40 ], Ethiopia [ 41 , 42 ], and Tanzania [ 43 ], this rate was different. The proportion of DC CMT in this study was high, and various risk factors, including housing, bedding, farm hygiene, mastitis history, milking method, milking machine cleanliness, and udder health monitoring, have been identified elsewhere [44–47].…”
Section: Discussionsupporting
confidence: 69%
“…It is estimated that approximately 68% of dairy cattle show an abnormal milk reaction using the CMT technique. This study found that the proportion of DC CMT in individual dairy cattle was similar to that found in Indonesia [ 39 ]; however, in contrast to other studies in Tunisia [ 40 ], Ethiopia [ 41 , 42 ], and Tanzania [ 43 ], this rate was different. The proportion of DC CMT in this study was high, and various risk factors, including housing, bedding, farm hygiene, mastitis history, milking method, milking machine cleanliness, and udder health monitoring, have been identified elsewhere [44–47].…”
Section: Discussionsupporting
confidence: 69%
“…This could be attributed to intrinsic (age, lactation stage, breed, and parity) or extrinsic (pathogen, farm management, hygiene and sanitation, and milking procedures) factors [ 59 ]. In Indonesia, mastitis cases are associated with a lactation stage longer than 2 months, poor house cleanliness, and poor milking procedures [ 30 , 31 ]. Most dairy farmers perform hand-milking procedures often without washing, pre-dipping, or post-dipping treatment [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peradangan pada ambing akibat mastitis dikategorikan menjadi 2 jenis yaitu mastitis klinis dan subklinis. Mastitis subklinis merupakan penyakit yang paling sering menyerang sapi perah masa laktasi dan berpotensi menurunkan produksi sehingga menimbulkan kerugian ekonomi bagi peternak (Khasanah et al 2021). Pengobatan antibiotik mastitis klinis dan subklinis merupakan komponen kunci dari program pengendalian mastitis.…”
Section: ■ Pendahuluanunclassified